Evaluasi dan Perbaikan User Interface Aplikasi Mobile GOBIS Suroboyo Bus berdasarkan Usability Testing menggunakan Metode Design Thinking - Riefqi Ardhya Bisma; Lutfi Fanani; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Golek Bis (GOBIS) Suroboyo is a public service application developed by the Surabaya Transportation Department (DISHUB Surabaya) in 2018 to improve the commuter experience with the public transportation networks. Although this application has been downloaded more than 100 thousand times by Android users in Indonesia, various users' complaints can still be found on the review page. The problem is strengthened by the interview data from several GOBIS Application users. They complain about the experience of dealing with uncertainty, difficulty finding the nearest bus stop, and feeling annoyed with appearing pop-up messages every time they return to the main page. Therefore, usability testing was carried out using the design thinking method to gain a deeper understanding of the problem and improve the design solution by considering the eight golden rules. The evaluation is measured based on three usability aspects: effectiveness, efficiency, and user satisfaction, which will be conducted in two stages, and then the results will be compared. After the research has completed, the effectiveness aspect increased to 100% on the whole task, the efficiency aspect increased ranging from 1.2 to 7.35 times faster, and the user satisfaction aspect increased ranging from 1.25 to 3.1 times better in the comparison of both evaluations of GOBIS Suroboyo Bus application.